Максимізація момента асинхронного двигуна в зоні високих швидкостей ротора за допомогою генетичного алгоритму - Приймак, Богдан Іванович (НТУ "ХПІ", 2013)
Is studied the problem of quality improving of the vector-controlled induction motor drives. Using genetic algorithm obtained a law forming of the rotor flux linkage that maximizes the torque of an induction motor with constraints voltage and stator current. Numerical studies have shown that the proposed law can significantly increase the motor torque in the area of high speed of rotor.
Maximization of induction motor torque in the zone of high speed of rotor using a genetic algorithm
Keywords: високі швидкості двигуна; потокозчеплення ротора; насичення магнітопроводу; метод параметричної оптимізації; Matlab